The influence of cultivation method on the soil’s organic carbon content calculations (Hungarian SOC reference values vs. IPCC defaults) - Kovács, Attila; Horváth, Bálint; Fogarassy, Csaba (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2014)
In the majority of the IPCC (Intergovernmental Panel on Climate Change) studies the third most significant segment among the activities of the agricultural enterprises is the GHG emission from the soil. It is important to examine how this value could be reduced. Our research aims to find the modeling system which is able to provide us with accurate data regarding the difference of the several cultivation methods and easy to apply on the basis of the facts of practical. IPCC methodology has been applied in the calculation specified with the results of certain Hungarian studies. As an early outcome we have come to see that in comparison with the regular methodology our results showed more precise values. Where the IPCC demonstrates 1-2 t CO2e we were able to witness 8-10 t CO2e on soils with better humus content. Therefore we concluded that accurate values of the changes can only be calculated with the involvement of the local conditions.